Investigating epistemic justice in an adaptive planning process: towards developing a local catchment management strategy - Ralekhetla, Mateboho Mary (Rhodes University, Faculty of Science, Institute for Water Research, 2019)
In South Africa, Integrated Water Resource Management (IWRM) is being put into practice in a way that incorporates the belief that all stakeholders should be given a voice in decisions that affect them. Catchment Management Forums (CMFs) are the first place for stakeholder participation, supported by Catchment Management Agencies (CMAs). A key first task of a CMA is to develop of their Catchment Management Strategy (CMS). In this research, I consulted and worked with stakeholders in the Makana Water Forum (Makana Local Municipality, Eastern Cape, South Africa) throughout the process as they worked towards formulating their local CMS. Importantly, this study used insights from the community to focus on the inter- and intra-group interactions among the stakeholders who participated in the first step of Strategic Adaptive Planning. In the process, I explored epistemic contestations that occurred between different epistemic agents (participants) who may have held identity prejudices. The research aimed to allow voices, which could otherwise have been marginalised, to come out in ways that were not stigmatised through the written and personal reflective process. In doing this, the study tried to hear the voice of the oppressed speaker whose knowledge and lived experiences have been overlooked by the hearer's prejudice. Findings show that participants who were part of the CMS development process experienced epistemic justice. These findings further established that the addition of participant reflections enhanced the level of epistemic justice promoted by the Adaptive Planning Process (APP).
Keywords: Watershed management -- South Africa; Watershed management -- South Africa -- Moral and ethical aspects; Water resources development -- South Africa -- Eastern Cape; Water-supply -- South Africa -- Makhanda; Makana Water Forum (Makhanda, -- South Africa); Makana Municipality (Makhanda, -- South Africa)